Does coffee affect bowel recovery following minimally invasive colorectal operations? A three-armed randomized controlled trial - Nasseri, Yosef; Kasheri, Eli; Oka, Kimberly; Zhu, Ruoyan; Smiley, Abbas; Cohen, Jason; Ellenhorn, Joshua; Barnajian, Moshe (International journal of colorectal disease, 2023)
Purpose Previous studies have suggested that coffee may shorten the postoperative ileus period. We sought to evaluate the impact of both coffee and caffeine on shortening the return of postoperative bowel function following minimally invasive colectomy. Methods This was a single-center, randomized controlled clinical trial conducted in a tertiary hospital. Patients undergoing an elective robotic or laparoscopic small or large bowel operation were included in this study. Patients were randomized into one of three groups: warm water, decaffeinated coffee, and caffeinated coffee. Subjects were assigned to drink a 4-oz cup three times daily starting on postoperative day one. The primary endpoint was time to first bowel movement. Secondary endpoints included time to first flatus, length of hospital stay, and postoperative morbidity. Results A total of 99 patients were included in this study: 31 warm water, 31 decaffeinated coffee, and 37 caffeinated coffee. The groups were similar in age and sex ( p = 0.51 and 0.91, respectively). Mean ( SD ) time to the first bowel movement in days was 2.94 (1.4), 2.58 (1.2), and 2.86 (1.3), respectively ( p = 0.53). There were no significant differences observed in postoperative morbidity ( p = 0.52) between groups. Multivariate linear regression analysis did not reveal a statistically significant association between any interventions and time to first bowel movement or length of hospital stay. Conclusions Coffee (caffeinated or decaffeinated) does not expedite the return of bowel function following minimally invasive operation. Trial registration https://classic.clinicaltrials.gov/ct2/show/NCT02639728 NCT02639728.